Toshihiko Izutsu’s Approach to the Qur’an: A Semantic Analysis of the Term Ghuluw and Its Contextualization - Hubby Dzikrillah Alfani, Ilzam; Mukhsin, Mukhsin; Shihab, Muhammad Fahmi (Jurnal Riset Agama, 2024)
This study aims to explore the meaning of the term ghuluw in the Qur'an and its relevance in social contexts. This qualitative research employs library research with descriptive analysis based on Toshihiko Izutsu's semantic approach. The findings indicate that ghuluw carries fundamental meanings such as rising, increasing, exaggerating, and exceeding limits, and it refers to the behavior of the People of the Book who exhibit extremism in their religious practices. Its synonyms include ighraq, tasyaddud, and ifrat, while its antonyms are i'tidal and istiwa. In the pre-Qur'anic era, ghuluw lacked religious connotations and was used solely in literary contexts, such as poetry. In the Qur'an, the term appears twice, revealed in Madinah, and addressed to the People of the Book. Exegetes unanimously interpret it as excessive or transgressive behavior in religion. Tafsir Al-Munir notes that the behavior of ghuluw had existed since the era of Jahiliyyah Arabs, who claimed to adhere to the monotheistic teachings of their ancestor, Prophet Ibrahim A.S. In the modern context, ghuluw is relevant to three major social issues: excessive practices in worship by considering non-religious obligations as mandatory, blind glorification of figures or leaders, and excessive veneration of certain groups, leading to irrational sacrifices.